Best paper award at IEEE PES ISGT-Europe 2021 conference - Aristidou, Petros (My University, 2026)
Our paper Comparison of AC Optimal Power Flow Methods in Low-Voltage Distribution Networks received a best paper award at IEEE PES ISGT-Europe 2021 conference.
Keywords: Sciences